E-commerce consumer contracts and conflict of law issues / Arni Roswani Sa'bar Noralamin … [et al.] - Sa'bar Noralamin, Arni Roswani; Mohd Fadzil, Farah Syifaa; Rusling, Hani Yusra; Hamzah, Norazila (Faculty of Law, 2011)
This research analyzed conflict of law issues arising in e-commerce. The aim of this research is to analyze whether the private international law in Malaysia protects consumers in e-commerce consumer contracts namely jurisdiction, choice of law and enforcement of foreign judgment. Applying content analysis, the conflict of law in Malaysia is just a general law governing the three component of conflict of law which is jurisdiction, choice of law and enforcement of foreign judgment. Hence it does not place any significance in protecting consumers whereas 'e-commerce' transaction which is cross border in nature needs specific attention. Consumers will be confident if; i. The court of their home country has jurisdiction to hear the case; ii. The choice of law is of the consumers home country and is legislated; iii. Reciprocity principle must be opened up to more countries. It will be more effective if a consensus can be reached among the ASEAN countries on conflict of law as the law in the EU countries. Comparing the conflict of law of the UK as it is one of the members of the recommendation have been suggested as to how the conflict of law in Malaysia should be attuned to e-commerce transaction with special attention in protecting consumers.